Data Literacy im Wissenschaftsjournalismus – Facetten journalistischer Datenkompetenz und Fortbildungsbausteine zu deren Schulung (mathematica didactica, 2025)
The Stifterverband's Data Literacy Charter (2021) emphasises the importance of promoting data literacy. Journalists play a special role by disseminating data and facts and can make a significant contribution to shaping public opinion. Surprisingly, however, there are so far only anecdotal reports on typical errors in media representations but hardly any empirically verified findings on the data literacy of journalists. This article presents a training programme to promote science journalists' data literacy. The training was evaluated using pre- and post-tests, which provide an initial insight into which data literacy facets can be improved.